GROWTH, HISTOPATHOLOGY OF ORGANS AND SEMEN CHARACTERISTICS OF COCKS FED DIETARY ORGANIC ZINC SOURCE (2014)
Most divalent minerals in plants are bound as phytate resulting in poor bio-availability in monogastrics, while inorganic zinc is less available to animals than organic zinc. Dietary supplementation with organic zinc sources like Bioplex Zinc (BZ) has been found to be beneficial for male ducks and pigs. Information on the dietary effects of the use of BZ in cocks has not been adequately documented. Therefore, growth, organs histopathology and semen characteristics of cocks fed dietary BZ were evaluated. One-day-old Nera black cockerels (n=240) were allotted to four treatments containing 0, 100, 200 and 300 mg/kg of BZ in a completely randomised design with five replicates (n=12) at the starter, grower and finisher phases. The study lasted for 30 weeks to determine Daily Feed Intake (DFI), Daily Weight Gain (DWG), Feed Conversion Ratio (FCR) and Zinc Retention (ZR) using standard procedures. Blood (5 mL) was collected at 8, 16 and 24 weeks after treatment for leukocytes, glucose, cholesterol and triglycerides analyses using standard procedures. Semen characteristics, morphology of sperm cells, testicular morphometry and histopathology of testis, liver, kidney, ileum and spleen were assessed using standard procedures. Data were analysed using descriptive statistics, regression and ANOVA at 0.05.The DFI (174.5±1.4 g) and DWG (18.1±1.0 g) were significantly higher in birds on 300 mg/kg BZ at the finisher phase. The FCR (10.0±0.6 - 9.6±0.8) decreased with increasing levels of BZ. The ZR were 35.0±0.4, 44.0±0.1, 52.3±0.1 and 69.1±0.4 % for birds fed 0, 100, 200 and 300 mg/kg BZ respectively. Leukocyte counts (10-3/mm3) (14.7±0.01, 14.3±0.02 and 14.1±0.05) were significantly lowered in birds fed 100, 200 and 300 mg/kg respectively compared to the control (16.9±0.05). Serum glucose, cholesterol and triglycerides of cocks decreased with increasing BZ levels. Semen volume (mL) of birds fed 0, 100, 200 and 300 mg/kg BZ were 0.30±0.01, 0.30±0.004, 0.31±0.002 and 0.40±0.01 respectively and mass activity were not different among treatments. The birds fed 0, 100, 200 and 300 mg/kg of BZ recorded sperm motility of 77.0±0.1, 83.9±0.1, 84.6±0.3 and 88.1±0.4 % and live spermatozoa of 82.7±0.3, 86.7±0.3, 88.9±0.5 and 90.3±0.2 % respectively. Sperm concentration (sperm cell/mL) (0.31±0.002, 0.33±0.003 and 0.45±0.001x109) respectively was higher in birds fed 100, 200 and 300 mg/kg of BZ than the control diet (0.29±0.008 x109). Spermatozoa with rudimentary tails (%) (1.7±0.03, 1.4±0.02, 1.3±0.01 and 0.7±0.02) and curved mid-piece (%) (1.3±0.02, 1.2±0.01, 1.2±0.02 and 0.6±0.01) decreased as the BZ increased. The paired testicular weights (g) (29.4±4.7, 25.2±7.4 and 28.1±5.7), volume (cm3) (25.8±8.2, 24.2±8.9 and 29.8±6.2) and density (g/cm3) (2.3±0.4, 2.1±0.9 and 1.9±0.2) of birds fed 100, 200 and 300 mg/kg BZ were not different from the control (27.8±10.2, 26.4±8.6 and 2.1±1.0) respectively Histopathology of kidney from 300 mg/kg BZ showed renal congestions while testis, liver, spleen showed no visible lesions across treatments. The 81% of the variation in DFI was explained by inclusion levels of BZ. Bioplex zinc increased growth rate, improved semen quality and reduced sperm cell abnormalities in cocks fed at 300 mg/kg